The Effect of Work Ability, Work Training, and Work Motivation on The Work Achievement of The Sragen State Prosecutor’s Employees : Article - Christina Heti Tri Rahmawati; Marselia Yunita Arum Pratiwi; Maria Angela Diva Vilaningrum Wadyatenti (Eastasouth Institute, 2022)
The quality of human resources is a company asset to produce optimal performance so as to improve employee performance. The purpose of the study was to measure the effect of work ability, work training, and work motivation on the work achievement of the Sragen Public Prosecutor's Office employees. The sampling technique used was saturated sampling. Data collection techniques used interviews with employees of the Head of Department of Administrative and Bureaucratic Reform and the Public Prosecutor's Office of Sragen as well as distributing questionnaires totaling 54 employees. The data analysis technique is in the form of multiple linear regression analysis. The research shows that the results of work ability, work training, and work motivation have a significant effect on the work achievement of the Sragen Public Prosecutor's Office employees. The implications of the results of this research for the Sragen State Attorney's Office should improve work skills related to quickly completing work, work training related to the length of training time, and work motivation related to performance recognition so that employee work achievement increases.